Ahmadiyah, conflicts, and violence in contemporary Indonesia - Mariani, Nina (State Institute of Islamic Studies (STAIN) Salatiga, 2013)
This article examines conflicts and violence experienced by Ahmadiyah commu-nity in Indonesia after reformasi era. In spite of diversities among Muslims inIndonesia, Ahmadiyah (Jemaat Ahmadiyah Indonesia) has been experiencing someforms of violence both from other Muslims and government. The number ofviolence has risen dramatically after the issuing second fatwa from Majelis UlamaIndonesia in 2005 and the Joint Ministerial Decree (SKB) on Ahmadiyah. Thoseforms of violence are issuing decree on banning Ahmadiyah, sealing the mosquesand banning of doing religious activities, and mobbing the mosques and houses,including killing. Furthermore, this paper argues that Indonesiaâs goverment doesnot take its responsibility to protect its people particularly from minorities groups,even some local governments also do violence towards Ahmadiyah community.ArtikelÂ iniÂ membahasÂ konflikÂ danÂ kekerasanÂ yangÂ dialamiÂ olehÂ komunitasAhmadiyah di Indonesia setelah masa reformasi. Walaupun Muslim di Indonesiasangat beragam, Jemaat Ahmadiyah Indonesia mengalami beberapa bentukkekerasn baik dari Muslim yang lain maupun dari pemerintah. Jumlah kekerasnayang menimpa mereka meningkat tajam setelah dikeluarkannya fatwa sesat keduadari MUI pada tahun 2005 dan Surat Keputusan Bersama (SKB) tiga menteri mengenai Ahmadiyah. Berbagai bentuk kekerasan yang menimpa mereka yaitupengeluaran peraturan pelarangan keberadaan Jemaat Ahmadiyah di berbagaiprovinsi, penyegelan masjid dan pelarangan melakukan aktifitas keagamaan,penyeranganÂ masjid-Â masjidÂ danÂ rumah-rumahÂ wargaÂ Ahmadiyah,Â bahkanpembunuhan.Â SelainÂ itu,Â pemerintahÂ pusatÂ sepertinyaÂ tidakÂ melaksanakankewajibannya untuk melindungi warganya, terutama dari kalangan minoritasbahkan beberapa pemerintah lokal justru melakukan kekerasan terhadap wargaAhmadiyah di daerahnya.